Juridical Analysis Of Human Rights Protection For Indonesian Migrant Workers Shipped Illegally : Research Study At The Riau Islands Police Directorate - Salamun Salamun; Bachtiar Simatupang; Ramlan Ramlan; Soerya Respationo; Erniyanti Erniyanti (Badan Penerbit STIEPARI Press, 2024)
This research focuses on